Keragaman dan Prevalensi Nematoda Parasit Usus pada Monyet Ekor Panjang (Macaca fascicularis) di Kawasan Wisata “Masjid Saka Tunggal” - Edy Riwidiharso; Erie Kolya Nasution; Heru Triaji (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Nematode parasites generally found around the world. Research on intestinal parasitic nematodes in long-tailed monkeys (Macaca fascicularis) has been carried out in Cikakak Village, Banyumas Regency. The aims of the research was to find out the diversity and prevalence of Nematodes parasite on long tail monkey. Survey methods was used in this research with determine the eggs of the nematodes parasite on faeces of 30 adults and 30 adolescence of monkey. The results of the study found five types of intestinal parasitic nematodes classified as " Soil Transmitted Helminths " namely Strongyloides sp. Ascaris sp. Trichuris sp. Ancylostoma sp. Oeshopagustomum sp. The parasitic diversity index value (H ') indicates moderate (moderate) community stability. Parasitic nematodes in adolescent long-tailed monkeys are relatively similar to adult monkeys. The prevalence of long-tailed monkeys infected with parasitic nematodes is quite high at 40.5 ± 13.5. The prevalence of long-tailed monkeys in adolescence is higher than the prevalence of adult long-tailed monkeys, nematode infections in long-tailed monkeys in Cikakak Village are more single infections. It can be concluded that long tail monkey at Cikakak have been infected by Nematodes parasites and this result can be used to population management of long tail monkey at this area.